STRUKTUR, DIKSI, DAN KALIMAT DALAM TEKS CERITA FANTASI KARYA SISWA KELAS VII SMP NEGERI 27 PADANG - Mustika, Delfitria; Nursaid, Nursaid; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ The purpose of this research is to describe the following points. First, the text structure of fantasy story of class VII students of JHS 27 Padang. Second, the use of diction in the text of fantasy story of class VII students of JHS 27 Padang. Third, the use of sentences in the text of fantasy story of students of class VII JHS 27 Padang. This type of research was qualitative by using descriptive method. This research was conducted in Junior High School 27 Padang. This research data in the form of fantasy story texts obtained from the source of research data that is the document results of student tasks amount of 25 texts fantasy story. The instrument of this research ware the researcher herself. Data is analyzed by describing, analyzing, and discussing data based on theory. The results of this study are as follows. First, found three fantasy story text structure, that is orientation, complication, and resolution in writing of student of class VII of JHS 27 Padang. Secondly, there are two types of sentences that use direct sentences and indirect sentences in the text of fantasy tales written by the seventh graders of JHS 27 Padang. Based on the research results can be concluded two things. First, in writing texts fantasy story of the seventh grade students of JHS 27 Padang has used the three fantasy story text structure. The third structure of the fantasy story text, namely orientation, complications, and resolution.Â Kata kunci: struktur, diksi, kalimat, teks cerita fantasi